answersLogoWhite

0


Best Answer

(x - a) + (x - a) + (b) = 2 (x - a) + (b) = x - a + x - a + b = 2x - 2a + b

User Avatar

Wiki User

โˆ™ 2011-08-07 21:48:57
This answer is:
User Avatar
Study guides

Algebra

20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

โžก๏ธ
See all cards
3.75
โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…
865 Reviews

Add your answer:

Earn +20 pts
Q: What does x-a plus x-a plus b equal?
Write your answer...
Submit
Still have questions?
magnify glass
imp
Related questions

How do you find the answer of a number having its power as a fraction?

Suppose you have the expression Xa/b. Xa/b is equal to b√(Xa) that is, the bth root of (X to the power a). Equivalently, it is (b√X)a, that is (the bth root of X), raised to the power a.


Why exponent 0 is equal to 1 to this problem 1x2 exponent 0 is equals 1?

x to the power a divided by x to the power b = x to the power (a - b), ie xa/xb = xa-b. When a = b, xa/xb = 1 and a - b = 0 so xa-b = x0. Rearranging gives x0 = 1. This is true for ALL non-zero values of x.


How do you find the gradient of two points?

If A = (xa, ya) and B = (xb, yb) and xa is not equal to xb, then gradient of AB = (ya - yb)/(xb - xb).If xa = xb then the gradient is undefined.


Why is 10 power 0 equal to 1?

Any number to the power zero is equal to one. That can be derived from the following index law: xa*xb = xa+b (x not zero) Now let b = 0 so that the above becomes xa*x0 = xa+0 so xa*x0 = xa (since a+0 = a) That is, any number multiplied by x0 is the number itself. That can be true only if x0 is the multiplicative identity, that is, only if x0 = 1.


Why a number to the zero power is always equal to 1?

It is a consequence of the definition of the index laws. xa * xb = xa+b If you put b = 0 in the above equation, then you get xa * x0 = xa+0 But a+0 = a so that the right hand side becomes xa Thus the equation now reads xa * x0 = xa For that to be true for all x, x0 must be the identity element for multiplication. That is x0 = 1 for all x.


What does b plus a plus b-a equal?

b + a + b - a = 2b


What property allows you to rewrite xa xb as xa b?

associative


Why any number raised to power zero is 1?

This derives from one of the laws of indices which states that, for any x (not = 0), xa * xb = xa+b Put b = 0 Then xa * x0 = xa+0 = xa (because a + 0 = a) But that means that x0 is the multiplicative identity. And since that is unique, and equal to 1, x0 = 1. This is true for all x. Put


Why the exponent rule of zero equals one?

The exponent rule for multiplication is xa * xb = xa+b Now, if you put b = 0, then a+b = a so that the above reads: xa * x0 = xa which only works if x0 = 1.


What is x to the power of a plus 1 times x to the power of a plus 1?

The question is ambiguous: xa+1 * xa+1 = x2(a+1) or (xa + 1)(xa + 1) = x2a + 2xa + 1


Why is 6 raised to the 0 power 1?

Any number raised to the power 0 is 1. This follow from the law of multiplications of power: xa * xb = xa+b Now, if you put b = 0, you get xa + x0 = xa+0 and since a+0 = a, the right hand side is xa. So you have xa * x0 = xa and using the property of the multiplicative identity, xa = 1.


What does b plus b equal?

2b

People also asked

Simplify 5x - 8a plus 4a - 2x plus a?

View results